PLOSIVE CONSONANTS IN ENGLISH AND MINANGNESE - Firdayanti Firdaus (Universitas Potensi Utama, 2019)
This Study deals with plosive consonants in English and Minangnese. The method of research used was descriptive qualitative method. It was conducted to find out the similarities and differences between English and Minangnese plosive consonants in investigating the learning problems of English by Minangnese speakers. In conducting the data, documentary and recording technique were done. Then, the data were analyzed based on the four procedures of Randal Whitman (1970). Those are description, selection, contrast, and prediction. The findings indicate that there were similarities and differences between English and Minangnese plosive connsonants. The similarities are in the place of articulation at bilabial [b, p], alveolar [d], and velars [g, k] in initial and medial positions, and in their state of the vocal cords, having the same voiced and voiceless sound. The differences are in their numbers, allophones, final positions, aspirations, and the place of articulation at [t] sound, which is alveolar in English but it is dental in Minangnese.